Getting the Full Picture on Public Officials : A How-to Guide for Effective Financial Disclosure - Rossi, Ivana M.; Pop, Laura; Berger, Tammar (Washington, DC: World Bank, 2016)
Financial disclosure systems are a vital component of transparency. By now 161 countries around the world have introduced financial disclosure systems, becoming commonplace around the world. But, although the rules are on the books, many practitioners are still struggling with the intricacies of the rules and how to implement them in the socioeconomic, historical, and legal context of their own country. Little guidance is available to assist them. This book aims to fill that void and provide practitioners with practical scenarios to consider before deciding on a particular course of action.